Pop-up Book of the Satua Bali Kambing Takutin Macan to Enhance Cultural Literacy Among Elementary School Students - I Gede Agus Julio Pramana (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low cultural literacy of elementary school students, as indicated by their limited understanding of local culture in learning. The purpose of this study is to develop an instructional media in the form of Pop-up Book Satua Bali Kambing Takutin Macan to enhance the cultural literacy of third-grade elementary school students. This study employs the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included 19 third-grade elementary school students, two teachers, and two experts, namely a media expert and a subject matter expert. Data were collected through observation, interviews, questionnaires, and tests. Data analysis was conducted using descriptive quantitative methods to assess the feasibility and practicality of the media, as well as a t-test to determine its effectiveness in improving students' cultural literacy. The results indicate that the Pop-up Book Satua Bali Kambing Takutin Macan is highly feasible based on the assessments of media experts (94.2%) and subject matter experts (96%), both categorized as excellent. The media was also considered highly practical by users, with teachers rating it at 97.5% and students at 96.05%. The effectiveness test demonstrated a significant impact on students' cultural literacy, as evidenced by the t-test results showing a significance value of 0.01. Thus, the Pop-up Book Satua Bali Kambing Takutin Macan has proven to be an effective instructional media that supports the enhancement of third-grade elementary school students' cultural literacy.